Bovine Genital Mycoplasmosis - Doig, P. A. (1981)
Infection, lesions and clinical significance of Acheloplasmas, Mycoplasma bovis and Mycoplasma bovigenitalium in genital disease of cattle are described. A more detailed account is given of ureaplasma infections. Acute and chronic forms of granular vulvitis in both field and experimental disease are described as well as the role of the organism in abortion. Recovery rates of ureaplasma and mycoplasma from semen and preputial washings in bulls are outlined and their significance in disease is discussed. There are problems in differentiating pathogenic from nonpathogenic isolates. Methods are being developed to treat semen for these organisms. This paper provides a concise summary of clinical and microbiological aspects of bovine genital mycoplasmosis.